Aksilarna regija - Mlakar, Boštjan (Medicinski razgledi, 1998)
Topography and contents of the axilla and its relations to the neighbouring regions are presented. The axilla is a pyramidal region. Its apex continues into the lateral regionof the neck. It provides a passageway for the axillary artery, vein and the brachial plexus. The axilla contains six groups of regional lymph nodes.
Keywords: Axilla; aksilarna regija; anatomija; Anatomy and histology; histologija; Axillary artery; Axillary vein; Brachial plexus; Lymph nodes; Muscles